2009
DOI: 10.1007/s11999-009-0749-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Survival in Patients with Epithelioid Sarcoma: 441 Cases from the SEER Database

Abstract: Current stratification of prognosis in patients with epithelioid sarcoma (ES) is based largely on data reported by individual centers with a limited number of patients. We sought to identify the important prognostic parameters using the Surveillance, Epidemiology, and End Results (SEER) database. We identified 441 patients with ES in the database and extracted information regarding patient demographics and clinical characteristics. KaplanMeier, log-rank, and Cox regression were used for analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
81
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 41 publications
3
81
0
Order By: Relevance
“…23,24 In a recent review, positive prognostic indicators in epithelioid sarcomas included age younger than 16 years, local stage of disease, negative lymph node status and complete surgical resection. 25 The high rate of local recurrence and distant metastasis observed in epithelioid sarcoma necessitates the development of improved adjuvant systemic therapies. Given the presence of morphologic and immunophenotypic features suggesting epithelial differentiation and lack of effective therapies currently available, therapeutic strategies targeting EGFR are promising.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 In a recent review, positive prognostic indicators in epithelioid sarcomas included age younger than 16 years, local stage of disease, negative lymph node status and complete surgical resection. 25 The high rate of local recurrence and distant metastasis observed in epithelioid sarcoma necessitates the development of improved adjuvant systemic therapies. Given the presence of morphologic and immunophenotypic features suggesting epithelial differentiation and lack of effective therapies currently available, therapeutic strategies targeting EGFR are promising.…”
Section: Discussionmentioning
confidence: 99%
“…Jawad et al studied the SEER database and found the overall survival of ES to be 68% at 5 years and 61% at 10 years. [7] Asano et al reported 30% local recurrence rate with the median interval between surgery and first local recurrence as 25 months. [8] The distant metastasis rate varies between 40% and 57%.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of epitheloid carcoma is increasing, with a annual percentage change of 5.2% since 1973. In 2005, the incidence is estimated 0.4 case per million 11 . Epithelioid sarcoma affects mainly the subcutaneous tissues, fascia, or tendon sheaths of the extremities.…”
Section: Discussionmentioning
confidence: 99%
“…In epithelioid sarcoma, advanced age, male gender, proximal or axial location, depth, tumor size, mitotic figures, necrosis, vascular invasion, and tumor hemorrhage have been identified as adverse prognostic factors 11 . In addition, local recurrence, lymph node metastasis, and the extent of surgery were also associated with survival in some studies 6,11,12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation